Using Technology to Assess Individualized Education Plan Goal Progress During Virtual Learning. Issue 1 (March 2023) - Wade, Taryn; McConomy, M. Addie; Heiniger, Sarah; Root, Jenny; Hott, Brittany
The purpose of this article is to provide practical, research-based strategies for using technology to monitor Individualized Education Plan (IEP) goal progress. Steps in the assessment process and progress monitoring strategies are provided to support educators in meeting the needs of students and to communicate the performance results with families. Case studies, resources, and sample materials are provided.